Sclerotium rolfsii scleroglucan: effects of thermal, alkaline and ultrasonic degradation - Viñarta, Silvana Carolina (2011)
Scleroglucan is a neutral water-soluble β-1,3-β-1,6-glucan produced by Sclerotium rolfsii ATCC 201126 whose triple helical conformation can be turned into single coiled chains at high pH or temperature and/or in DMSO. Effects of thermal (65, 95 and 150ºC), alkaline (0·01-0·2 N NaOH) and ultrasonic (1, 5 and 10 min with 20% amplitude) treatments onto the solution properties of S. rolfsii scleroglucans (EPS I, EPS II and EPSi at 0·2% w/v) were comparatively evaluated vs. commercial scleroglucan (LSCL). The more drastic assayed conditions (150ºC, 0·2 N NaOH and 10-min ultrasonication) significantly modified the rheological behavior of scleroglucan solutions, with an abrupt decline in apparent viscosity and the loss of pseudoplastic behavior. EPS I was identified as the less sensitive polymer to thermal degradation, whilst EPSi and LSCL were particularly susceptible to alkaline treatment but the more stable ones against ultrasonication. Scleroglucan samples were all denatured (triple helix -> single brand transition) at 150°C and 0·2 N NaOH. Additionally, size exclusion chromatographic (SEC) profiles of control and treated polymer samples revealed aggregates, single chains and triple helices distinctive zones in accordance with the applied treatment.